The Mosque as an Agent of Social Welfare: Philanthopic Programs at Jogokariyan Mosque - Kurniawati, Neneng Nadila; Afief El Ashfahany; Khan, Mohammad Zahid (Suhuf: International Journal of Islamic Studies, 2025)
This article explores the role of Jogokariyan Mosque as an agent of social transformation in enhancing community welfare through Islamic philanthropic programs and community-based economic empowerment. Departing from the conventional function of mosques limited to ritual worship, Jogokariyan Mosque has evolved into a center of socio-economic integration that actively engages in uplifting the local community. Using a qualitative-descriptive method, this study examines the mosque’s strategic approaches, programmatic innovations, and the socio-economic impacts of its philanthropic activities. Findings reveal that Jogokariyan Mosque implements a comprehensive, data-driven social mapping system to design needs-based programs. It adopts a no-surplus financial policy, ensuring that zakat, infaq, and sadaqah (ZIS) funds are immediately allocated for entrepreneurship, education, and healthcare. Through these initiatives, the mosque facilitates the transformation of beneficiaries (mustahiq) into donors (muzakki) and strengthens social cohesion rooted in Islamic ethical values. The study highlights the potential of faith-based institutions to function as sustainable community empowerment centers. Further research is recommended to assess the scalability and long-term impact of such mosque-based models across diverse socio-cultural contexts.